Evidence on Efficacy and Safety of Chinese Medicines Combined Western Medicines Treatment for Breast Cancer With Endocrine Therapy - Li, Lu; Wang, Rongyun; Zhang, Aolin; Wang, Ling; Ge, Qianwen; Liu, Yuan; Chen, Tianhui; Wang, Chi Chiu; Leung, Ping Chung; Sun, Qiuhua; Fan, Xiaohui (Frontiers in Oncology, 2021)
Background Breast cancer, a malignant disorder, occurs in epithelial tissue of the breast glands and ducts. Endocrine therapy is commonly applied as an important adjuvant treatment for breast cancer, but it usually induces a variety of side effects. Chinese Medicines (CM) has therapeutic effect on reducing adverse effects of the endocrine therapy in many clinical studies. But strong evidence is still limited on the efficacy and safety of CM combined western medicines (CM-WM) for breast cancer. Objective To study the efficacy and safety of CM-WM as an adjuvant treatment for reducing side effects induced by endocrine therapy in breast cancer patients. Method We searched relevant clinical studies in PubMed and the Chinese National Knowledge Infrastructure (CNKI) databases up to February 28, 2021 and only Randomized Controlled Trials (RCTs) were included. There were no limitations on the languages. We extracted data from the included RCTs, assessed study quality, conducted meta-analyses by RevMan 5.4 and compared the pooled Risk Ratios (RR) or Mean Difference (MD) with 95% CIs. Results In total 28 trials involving 1,926 participants were included. Six RCTs compared CM-WM with CM placebo-WM, while 22 RCTs compared CM-WM with WM alone. No study compared CM-WM with no treatment. Meta-analysis showed that CM-WM treatment significantly improved quality of life (MD = 0.73, 95% CI = 0.11–1.35, P = 0.02) when compared with CM placebo-WM treatment. When compared with WM treatment alone, CM-WM treatment significantly improved bone mineral density (MD = 0.24, 95% CI = 0.13–0.35, P <0.0001), TCM syndrome score (MD = −5.39, 95% CI = −8.81 to −1.97, P = 0.0002), Kupperman Scale (MD = 0.24, 95% CI = −2.76 to −1.94, P <0.0001), Karnofsky Performance Scale (MD = 3.76, 95% CI = 1.64–5.88, P = 0.0005), quality of life (MD = 3.01, 95% CI = 1.00–5.02, P = 0.003), and pain relief (MD = 2.10, 95% CI = 0.72–3.48, P <0.0001). Compared with WM, CM-WM significantly decreased incidence of TCM symptoms (nausea, vomiting, fatigue, etc.) (RR = 1.60, 95% CI = 1.40–1.84, P <0.0001). For safety, serum calcium, estradiol, ALP, and blood CD3, CD4 and CD8 counts were not significantly difference between two treatments (P >0.05). Serious side effects or reactions were not reported in all included studies. Conclusion The adjunctive use of CM reduced the endocrine therapy associated adverse events, including bone mineral density loss, perimenopausal symptoms, poor quality of life, pain and impaired immune function. But large-scale and high quality RCTs are needed to support the application of CM-WM therapy.